2005
DOI: 10.1128/aac.49.3.931-944.2005
|View full text |Cite
|
Sign up to set email alerts
|

Global Expression of Prophage Genes in Escherichia coli O157:H7 Strain EDL933 in Response to Norfloxacin

Abstract: We investigated the influence of a low concentration of the gyrase inhibitor norfloxacin on the transcriptome of enterohemorrhagic Escherichia coli O157:H7 strain EDL933. For this purpose, we used a commercial DNA microarray containing oligonucleotides specific for E. coli O157:H7 strains EDL933 and RIMD0509952 and E. coli K-12 strain MG1655. Under the conditions applied, 5,963 spots (94% of all spots) could be analyzed. Among these, 118 spots (P < 0.05) indicated transcriptional upregulation and 122 spots (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 57 publications
7
64
1
Order By: Relevance
“…In accordance with other authors (20), we hypothesized that the expression of phage genes may be regulated when other temperate phages are present. We examined in an E. coli K-12 background the effect on phage and toxin production when the same host strain was converted by one or two Stx prophages.…”
supporting
confidence: 54%
“…In accordance with other authors (20), we hypothesized that the expression of phage genes may be regulated when other temperate phages are present. We examined in an E. coli K-12 background the effect on phage and toxin production when the same host strain was converted by one or two Stx prophages.…”
supporting
confidence: 54%
“…Effectively, in a study that investigated global gene expression during growth transitions of E. coli O157:H7, the transcript levels of stx2A decreased 1.5-fold from late exponential to stationary phase, while levels of stx2B remained higher in stationary phase than in exponential phase (5). In contrast, when global expression of EDL933 in response to norfloxacin was obtained, the transcript levels of stx2A were at least twice as high as those of stx2B (25).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a sub-inhibitory concentration against environmental bacteria is still unknown. It was reported that FQs at concentrations 10-100 times weaker than the MIC induced the expression of a functional gene (16), mutations (11), and morphological changes (33) at the single cell level. The concentrations detected in this study were lower than those.…”
Section: Discussionmentioning
confidence: 99%